Social status, volunteering, and community engagement: Matching messages to self- and other-oriented motivations - Hyun-Suk Lee; Mark Snyder; Hyun Euh (Cogent Psychology)
Building on previous research and theory on volunteerism, three pre-registered studies used message matching techniques to investigate the effects of self-focused messages (emphasizing the benefits to the volunteers) and other-focused messages (emphasizing the benefits to the recipients) and social status in promoting volunteerism. Participants, randomly assigned, read either self-focused messages or other-focused messages that contained information about an opportunity to volunteer to help people in poverty. Then, they completed a set of self-report measures on the prospect of volunteering, intentions to volunteer, attitudes toward volunteering, empathy toward the recipients, and anticipated costs of becoming a volunteer. They also reported their perceived social status and household income. However, we did not find evidence that matching self-focused messages to individuals of higher status and other-focused messages to lower status individuals promoted volunteerism. The overall pattern of results suggests only limited effects of message matching with self- and other-oriented motivations across individuals with differing socioeconomic backgrounds. Building on this overall pattern of findings, we discussed the roles of social status, volunteer experience, and persuasive messages in promoting volunteerism.